STRUKTUR DAN ROMANTISME DALAM KUMPULAN CERPEN KIDUNG KAMPUNG BERDEBU KARYA SAIFUN ARIF KOJEH - Juniawati, Anggi; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research focused on form of structure and romanticsm in Kidung Kampung Berdebu short story colecction written by Saifun Arif Kojeh. The research work tried to find out structure of short story, romanticism, and implementation of the short story at school. The researc hopefully benefits school to give knowledge, develop research in prose, provide materials, and be reference for next research in prose to streghten research work in prose in West Kalimantan.The research eployed decriptive qualitative methodelogy using structuralism approach. The data was taken from text of in Kidung Kampung Berdebu short story collection, then was analysed based on the approach used. The research finding showed that most structure forms in the short story are love and friendship theme. The background are taken from daily activities. In addition, the characters tend to be protagonist, the plot is chronological, and the massage is related to social life. In aspect of romanticism, the story tends to describe environment, melancholy, primitivism shown by extreme metal state, sentimentality shown by anger and sarcasm, individuality shown by loneliness, and exoticism.Keywords:       Structure, Romanticsm, & Short Story